2015
DOI: 10.3386/w21597
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks, Ethnicity, and Entrepreneurship

Abstract: We study the relationship between ethnicity, occupational choice, and entrepreneurship. Immigrant groups in the United States cluster in speci…c business sectors. For example, Koreans are 34 times more likely than other immigrants to operate dry cleaners, and Gujarati-speaking Indians are 108 times more likely to manage motels. We develop a model of social interactions where non-work relationships facilitate the acquisition of sector-speci…c skills. The resulting scale economies generate occupational strati…ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 41 publications
2
33
0
5
Order By: Relevance
“…These reduced outside options may make immigrants willing to launch a business of any form and venture into riskier domains. A third, more positive, possibility is that the tight social structures for some immigrant groups allow them a group-based capacity to enter into riskier domains and rely on each other, similar to the studies of immigrant entrepreneurial specialization (e.g., Kerr and Mandor¤, 2015).This comparative advantage could be consistent with bene…ts of immigrantgenerated diversity documented by Ottaviano and Peri (2006), Mazzolari and Neumark (2012), Nathan (2015), and similar. Another possibility, to complete a …rst and incomplete list, is that illegal immigration and undocumented workers in immigrant-led …rms have somehow led us to mismeasure some of the growth/survival properties.…”
supporting
confidence: 69%
“…These reduced outside options may make immigrants willing to launch a business of any form and venture into riskier domains. A third, more positive, possibility is that the tight social structures for some immigrant groups allow them a group-based capacity to enter into riskier domains and rely on each other, similar to the studies of immigrant entrepreneurial specialization (e.g., Kerr and Mandor¤, 2015).This comparative advantage could be consistent with bene…ts of immigrantgenerated diversity documented by Ottaviano and Peri (2006), Mazzolari and Neumark (2012), Nathan (2015), and similar. Another possibility, to complete a …rst and incomplete list, is that illegal immigration and undocumented workers in immigrant-led …rms have somehow led us to mismeasure some of the growth/survival properties.…”
supporting
confidence: 69%
“…Boubtane, Dumont and Raul (2015) reported that 1 percentage point increase in migrant's share of labour force is associated with 0.4-0.5 percent rise in productivity. This is rooted, at least partially, in occupational stratification as mentioned above (Kerr & Mandorff, 2015).…”
Section: Economic Impact Of Labour Migration On the Receiving Countriesmentioning
confidence: 90%
“…This reliance on personal networks may be the result of extreme information asymmetry between founders and VC investors (e.g. Stuart & Sorenson 2005, Hochberg, Ljungqvist & Lu 2007, Kerr & Mandorff 2015. However, heavy reliance on trusted referrals may also privilege those who are more connected to investors (Cohen, Frazzini & Malloy 2008).…”
Section: Introductionmentioning
confidence: 99%